Butanol Fraction of Olax Subscorpioidea Produces Antidepressant Effect: Evidence for the Involvement of Monoaminergic Neurotransmission - Adeoluwa, Adebayo O.; Aderibigbe, Oladele A.; Agboola, Isaiah O.; Olonode, Toyin E.; Ben-Azu, Benneth (Drug Research, 2019)
This study sought to investigate involvement of monoaminergic mechanism in the antidepressant action of butanol fraction (BF) of Olax subscorpioidea in rodents and the bioactive principles present. Butanol fraction was evaluated for antidepressant-like effect in the tail suspension, forced swimming and open field tests. All animals were treated with BF (5, 10 & 20 mg/kg) thirty minutes prior to the tests. On the other hand, monoaminergic neurotransmission involvement was probed by pre-treating animals with yohimbine hydrochloride (1 mg/kg, α2 antagonist), prazosin (62.5 µg/kg, α1 antagonist), propranolol (2 mg/kg, non-selective β antagonist), sulpiride (50 mg/kg, D2 receptor blocker), haloperidol (0.2 mg/kg, non-selective D receptor blocker), metergoline (4 mg/kg, i.p., a 5HT-receptor blocker) and PCPA (100 mg/kg, i.p., inhibitor of tryptophan hydroxylase), fifteen minute before treatment with BF (10 mg/kg). Identification of the major bioactive constituents was done by HPLC. The findings show that BF (5 & 10 mg/kg) significantly decreased immobility in despair tests of depression without effect on locomotor activity. The data also shows that anti-immobility effect of BF (10 mg/kg) in the TST was reversed by prazosin, yohimbine, haloperidol, sulpiride, metagoline and PCPA but not with propranolol. Bioactive principles present are caffeic acid, rutin, morin and quercetin. In conclusion, our findings show that BF produces antidepressant-like effect, which may be dependent on its interaction with the monoaminergic system.
Keywords: Olax subscorpioidea; Olacecae; monoaminergic transmission; depression